2019
DOI: 10.18480/jjae.21.0_63
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Staple Food Prices in Ethiopia: Does Warehouse Service Matter?

Abstract: Using 128 domestic and international monthly price series offour commodities, this study demonstrates how and to what extent warehouse service affects seasonality of food prices in Ethiopia. The study also examines the characteristics and degree of food price seasonality in the country. Our result shows that there is significant variation in the seasonal gap amongst crops-i.e. the highest seasonal gap being for maize (20%). We also find that 10-14% of monthly price volatility in Ethiopia is explained by its se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…They also have some limitations, especially the potential introduction of upward bias with short time series such as our dataset (see Gilbert et al (2017) for a comprehensive discussion). Trigonometric models have been shown to address some of these limitations because they are parsimonious in the number of parameters needed for estimation and are less prone to biased gap estimation, especially for shorter time series (Ray et al 2001;Kaminski et al 2016;Bai et al 2020;Kotu et al 2019;Wassie, Kusakari and Sumimoto 2019). Following Gilbert et al (2017) and comparing both methods, we also found the trigonometric method to be preferred by model fit statistics (Supplementary Table F) for the food price dataset.…”
Section: Seasonalitymentioning
confidence: 59%
See 1 more Smart Citation
“…They also have some limitations, especially the potential introduction of upward bias with short time series such as our dataset (see Gilbert et al (2017) for a comprehensive discussion). Trigonometric models have been shown to address some of these limitations because they are parsimonious in the number of parameters needed for estimation and are less prone to biased gap estimation, especially for shorter time series (Ray et al 2001;Kaminski et al 2016;Bai et al 2020;Kotu et al 2019;Wassie, Kusakari and Sumimoto 2019). Following Gilbert et al (2017) and comparing both methods, we also found the trigonometric method to be preferred by model fit statistics (Supplementary Table F) for the food price dataset.…”
Section: Seasonalitymentioning
confidence: 59%
“…;Kaminski, Christiaensen and Gilbert 2016;Bai et al 2020;Kotu et al 2019;Wassie, Kusakari and Sumimoto 2019) Gilbert et al (2017). find the more parsimonious trigonometric method to be preferable for food price data.…”
mentioning
confidence: 99%
“…Estudos recentes utilizaram dois componentes harmônicos de primeira ordem, o que permitiu captar a sazonalidade anual dos preços (Gilbert et al, 2017;Wassie et al, 2019). Entretanto, uma série de Fourier de primeira ordem impõe simetria no padrão sazonal, o que não é interessante para a presente pesquisa, uma vez que, geralmente, a sazonalidade dos preços agrícolas não apresenta esse comportamento.…”
Section: Modelo Harmônicounclassified
“…Ou seja, o crescimento da produção foi "puxado" pela safra de inverno, tornando-se a safra dominante do padrão sazonal nessa região. Vale observar, por fim, que a diferença observada foi próxima a estudos realizados em países africanos, como os realizados por Kaminski et al (2016) e Wassie et al (2019), os quais obtiveram um intervalo sazonal para o milho entre 20% e 30%.…”
Section: Análise Com Três Períodosunclassified
See 1 more Smart Citation